"Synthesis, Spectral Characterisation, Theoretical Investigations and Nonlinear Optical Properties of Ethyl 4‐(3‐(1, 3‐dimethyl‐1H‐pyrazole‐5‐carboxamido)phenyl)‐1, 2, 3, 4‐tetrahydro‐6‐methyl‐2‐oxopyrimidine‐5‐carboxylate". Issue 32 (13th November 2017) - Adaikalaraj, Chinnapan; Manivarman, Subramanian
Abstract: Newly synthesized nonlinear optical material is ethyl4‐(3‐(1, 3‐dimethyl‐1H‐pyrazole‐5‐carboxamido)phenyl)‐1, 2, 3, 4‐tetrahydro‐6‐methyl‐2‐oxopyrimidine‐5‐carboxylate (DMPC). It has been characterized experimentally by FT‐IR, FT‐Raman, 1 H and 13 C‐NMR spectrum and theoretically by DFT method using B3LYP/6‐31G(d, p) level of theory. A detailed interpretation of the vibrational spectrum was comparable with theoretical wavenumber using single scaling factor. The intra‐molecular charge transfers occurring in the molecule have been analyzed by donor‐acceptor interaction from natural bonding orbital analysis. The nonlinear optical activity of the compounds has been calculated, and found that the molecule is a good candidate of nonlinear material. The optical response and conduction nature of the title molecule have band gap of frontier edges were calculated by TD‐DFT calculation and these results studied with UV‐Visible spectrum. Especially the π‐π* bonding interactions were interested to study conjugative property of the molecule. Moreover, molecular electrostatic potential surface of DMPC are useful in investigating the stability and reactivity of the molecule Abstract : In title molecule, the calculated N4 ‐N9 bond length 1.3456 Å is very shorter than the usual pyrazoline N−N bond length 1.395 Å because, methyl group is directly substituted at N9 atom. The formation of title molecule by intra‐molecular hyperconjugative interaction of LP (N15 ) → π*C14 −O16 which increases D(0.3342) that weakens the respective anti‐bonds leading to highest stabilization of 263.17 kJ/mol. The first hyperpolarizabilty (β0 ) 5.0862 x10 −30 esu of the title compound is fourteen times greater than that of urea. It is responsible for the lowest band gap (4.7279 eV) value.